2019
DOI: 10.15294/kemas.v15i1.12111
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Respiratory Symptoms Caused by Chemical Hazard on Hairdresser Workers in Palembang

Abstract: Respiratory Disease is the leading cause of death in the majority of people and is among the top 10 causes of death in the world. Factors causing respiratory disease are occupational exposure, smoking and lung infections. According to WHO, 65 million people have respiratory illnesses ranging from moderate to severe. Nearly 90% of deaths from respiratory illness occur in low- and middle-income countries. Hairdressers are exposed to many chemicals in the use of many hair products such as shampoos, curling produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…It is noteworthy that the majority of individuals who engage in hairdressing activities are women, and this study confirmed that the majority of hairdressers were women (62.0%). This is consistent with the findings of previous studies 10 42. This high prevalence of respiratory diseases in women can be explained by the fact that, in addition to their hairdressing occupations, women also cook at home, which is associated with the risk of air pollution from cooking fuels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is noteworthy that the majority of individuals who engage in hairdressing activities are women, and this study confirmed that the majority of hairdressers were women (62.0%). This is consistent with the findings of previous studies 10 42. This high prevalence of respiratory diseases in women can be explained by the fact that, in addition to their hairdressing occupations, women also cook at home, which is associated with the risk of air pollution from cooking fuels.…”
Section: Discussionsupporting
confidence: 92%
“…9 More than 90% of deaths occur in low-income and middle-income countries. [9][10][11] Epidemiological studies have identified high-risk jobs and hazardous exposures. 10 In low-income countries, including Ethiopia, where most patients have access to poor healthcare services, occupational respiratory morbidities are emerging as public health problems.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations